2013
DOI: 10.1007/s10616-013-9540-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ottoman Viper (Montivipera xanthina (Gray, 1849)) Venom on Various Cancer Cells and on Microorganisms

Abstract: Cytotoxic and antimicrobial effects of Montivipera xanthina venom against LNCaP, MCF-7, HT-29, Saos-2, Hep3B, Vero cells and antimicrobial activity against selected bacterial and fungal species: Staphylococcus aureus ATCC 25923, Escherichia coli ATCC 25922, E. coli O157H7, Enterococcus faecalis 29212, Enterococcus faecium DSM 13590, Staphylococcus epidermidis ATCC 12228, S. typhimirium CCM 5445, Proteus vulgaris ATCC 6957 and Candida albicans ATCC 10239 were studied for evaluating the potential medical benefit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 24 publications
3
30
0
Order By: Relevance
“…Therefore, it was suggested to use different methods in combination to assess cytotoxicity. 31 Selective cytotoxic effect of Anatolian M. lebetina obtusa against various cancer cell lines (not including leukemia) has been reported previously 26 and shown to be po- 26,30 Therefore, the cytotoxic potency of the venom on various cancer cell lines should be determined by an initial screening study. It has been reported that crude venom of M. lebetina (subspecies could be assigned as M. lebetina turanica, according the origin of the samples stated in the paper) inhibited the viability of K562 cells about 10% after treating with 50 µg/mL of venom for 72 h. 19 According to our results, M. l. obtusa venom was more potent on K562 cells, compared to M. l. turanica venom.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Therefore, it was suggested to use different methods in combination to assess cytotoxicity. 31 Selective cytotoxic effect of Anatolian M. lebetina obtusa against various cancer cell lines (not including leukemia) has been reported previously 26 and shown to be po- 26,30 Therefore, the cytotoxic potency of the venom on various cancer cell lines should be determined by an initial screening study. It has been reported that crude venom of M. lebetina (subspecies could be assigned as M. lebetina turanica, according the origin of the samples stated in the paper) inhibited the viability of K562 cells about 10% after treating with 50 µg/mL of venom for 72 h. 19 According to our results, M. l. obtusa venom was more potent on K562 cells, compared to M. l. turanica venom.…”
Section: Discussionmentioning
confidence: 93%
“…14,20,26,30,34 These studies resulted in the description of venom proteins possessing in vitro and/or in vivo anticancer activity, including disintegrin, metalloproteinase, CLP, PLA 2 , and LAAO. Anticancer properties of snake venom proteins and their therapeutic potential have been reviewed recently by various authors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies on the biological and proteomic characterization of various viper venoms in Turkey have been carried out (Igci & Demiralp 2012;Nalbantsoy et al 2012Nalbantsoy et al , 2013Topyıldız & Hayretdag 2012;Yalcin et al 2014). As a contribution to the authors' ongoing studies on Turkish venomous snakes, the aim of this study was to screen the cytotoxic and antimicrobial activities of Anatolian M. l. obtusa crude venom on various cancer cells and microorganisms, to assess its potential as a source of bioactive peptides/proteins which may have therapeutic value.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, studies on biological and proteomic characterization of various viper venoms have been done in Turkey (Igci and Demiralp, 2012;Nalbantsoy et al, 2013;Yalcin et al, 2013).…”
mentioning
confidence: 99%